PENDAMPINGAN PEMASARAN DIGITAL UNTUK UMKM: STRATEGI EFEKTIF DALAM MENINGKATKAN BRAND AWARENESS DAN PENJUALAN DI DESA GEDANGAN - Sugeng , Suprapto; Arifudin, Muhammad Aan (COMVICE: Journal Of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy, but often face challenges in increasing brand awareness and sales. Digital marketing is an effective solution to expand market reach at a relatively affordable cost. This activity discusses digital marketing facilitation strategies for MSMEs, including the use of social media, search engine optimization (SEO), content-based marketing, and digital advertising. Through case study methods and literature analysis, it was found that a structured and data-based approach can significantly increase brand visibility and sales conversions. In addition, the use of digital platforms allows direct interaction with consumers, builds loyalty, and creates a more personalized shopping experience. By adopting the right digital marketing strategy, MSMEs can compete more competitively in the global market. This activity recommends training, mentoring, and policies that support the digitalization of MSMEs to increase competitiveness and sustainable business growth.